Optical fibers for bio-sensing applications. (January 2019) - Talataisong, Wanvisa; Ismaeel, Rand; Lee, Timothy; Beresna, Martynas; Brambilla, Gilberto
Abstract: Here we discuss several different pathways of exploiting optical fibers for sensing applications. We demonstrate that fused optical fiber couplers can operate as a sensitive refractometers and thermometers. Their potential for bio-sensing applications is also discussed. We also discuss application of plastic fibers for accessing mid-IR spectral region for optical sensing.